An Experimental Study of the Hydrodynamic Characteristics of Curved Blade Undershot Water Wheels for Laboratory-Scale Irrigation - Buku, Atus; Yandi, Nurul Utami Sri Putri (Engineering, Technology & Applied Science Research, 2026)
This study investigates the hydrodynamic and performance characteristics of a laboratory-scale curved-blade undershot water wheel under varying inlet flow velocities, upstream water levels, and bucket configurations (6, 8, 10, and 12 buckets). Experiments were conducted using a recirculating open-channel system to evaluate rotational speed and bucket discharge under steady-state conditions. The results show that rotational speed increases proportionally with flow velocity due to greater kinetic energy transfer. At 0.565 m/s, the 6-bucket configuration achieved the highest angular velocity of 0.665 rad/s, while the 12-bucket configuration produced the lowest velocity of 0.305 rad/s, indicating a torque–speed trade-off associated with increased water mass loading. Increasing the water level from 0.042 m to 0.050 m enhanced bucket discharge from 5.9 × 10⁻⁶ m³/s to 7.5 × 10⁻⁶ m³/s for 12 buckets; however, it reduced rotational speed due to higher gravitational torque resistance. Bucket discharge was directly proportional to both inlet flow rate and bucket number; however, excessive bucket density introduced hydrodynamic interference, suggesting an optimal configuration. These findings demonstrate that water wheel performance is governed by the interaction between hydraulic input parameters and geometric design, highlighting the importance of optimizing bucket number for low-head irrigation and pico-hydropower applications.